2005
DOI: 10.1111/j.1365-2702.2005.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Greek version of Kogan's Old People Scale

Abstract: Nursing education--basic and lifelong--needs to be updated in order to respond to the needs of older people and a reliable instrument can help to evaluate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 15 publications
5
37
1
6
Order By: Relevance
“…RNs reported a higher positive score compared to both nurses and CNAs. These results confirm those of other authors 22,23,26,27 who demonstrate that a higher level of education and the age of respondents relate to positive attitudes toward older persons and therefore, preferences for working within the field of elder care are likely to increase. One possible explanation for the high positive attitude as well as the low negative attitude among RNs may be that baccalaureate nursing programs in Sweden have aimed to provide stand-alone courses in gerontological care in recent years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RNs reported a higher positive score compared to both nurses and CNAs. These results confirm those of other authors 22,23,26,27 who demonstrate that a higher level of education and the age of respondents relate to positive attitudes toward older persons and therefore, preferences for working within the field of elder care are likely to increase. One possible explanation for the high positive attitude as well as the low negative attitude among RNs may be that baccalaureate nursing programs in Sweden have aimed to provide stand-alone courses in gerontological care in recent years.…”
Section: Discussionsupporting
confidence: 91%
“…The KOPS has been translated into several languages, 21,22 including Swedish. 19 The questionnaire consists of 17 positive (OP + ) statements and 17 negative (OP -) statements and uses a five-point Likert scale with response options on both the positive and negative statements ranging from strongly agree to strongly disagree.…”
Section: Survey Questionnairementioning
confidence: 99%
“…The small change in attitudes on the OP from moderately neutral to slightly positive in this study is consistent with other research [4,6,7,12,15,30] . These results suggested that nurses with a higher level of education acquire more positive attitudes towards older people [31] .…”
Section: Discussionsupporting
confidence: 82%
“…The Kogan's Old People Scale has been translated into several languages (Lambrinou, Sourtzi, Kalokerinou, & Lemonidou, 2005;Yen et al, 2009) including Swedish (Lindencrona, 1987) with an internal consistency for the whole scale of .79 (Kogan, 1961;Lindencrona, 1987). For the positive and negative statements, the internal consistency statements range from .66 to .77 and from .73 to .83, respectively (Söderhamn, Lindencrona, & Gustavsson, 2001).…”
Section: Survey Questionnairementioning
confidence: 99%